2007
DOI: 10.1186/1471-2164-8-19
|View full text |Cite
|
Sign up to set email alerts
|

The dystrotelin, dystrophin and dystrobrevin superfamily: new paralogues and old isoforms

Abstract: Background: Dystrophins and dystrobrevins are distantly related proteins with important but poorly understood roles in the function of metazoan muscular and neuronal tissues. Defects in them and their associated proteins cause a range of neuromuscular disorders. Members of this superfamily have been discovered in a relatively serendipitous way; we set out to compile a comprehensive description of dystrophin-and dystrobrevin-related sequences from available metazoan genome sequences, validated in representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 75 publications
1
41
0
1
Order By: Relevance
“…A similar myoseptal localization has been reported for other Integrin-adhesion complex mRNAs in the zebrafish embryo [3436]. In addition, Dystroglycan complex proteins, also involved in cell-ECM adhesion, show transcript enrichment at the vertical myosepta similar to pxnb [37]. Intriguingly, local accumulation and translation of myosin mRNA has been demonstrated at sites of myoblast adhesion in culture in response to contractile forces [38].…”
Section: Resultssupporting
confidence: 63%
“…A similar myoseptal localization has been reported for other Integrin-adhesion complex mRNAs in the zebrafish embryo [3436]. In addition, Dystroglycan complex proteins, also involved in cell-ECM adhesion, show transcript enrichment at the vertical myosepta similar to pxnb [37]. Intriguingly, local accumulation and translation of myosin mRNA has been demonstrated at sites of myoblast adhesion in culture in response to contractile forces [38].…”
Section: Resultssupporting
confidence: 63%
“…It has been shown that the transcription factor HSF1 is essential to neurogenesis and spinogenesis in the dentate gyrus of the hippocampus and to the development of normal emotional and social behavior (Uchida et al 2011). As one of the most widely expressed isoforms of dystrophin (Jin et al 2007), Dp71 forms the dystrophin-associated protein complex (DAPC) in non-muscle tissues via association with dystroglycans, sarcoglycans, dystrobrevins, syntrophins, and accessory proteins. Mental retardation and retinal dysfunction are the two main phenotypes closely associated with Dp71 involved in DMD.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis of mouse trigeminal and sciatic nerves detected doublet bands in the region of 116 kDa [13]. In silico analysis found that additional 14 amino acids in human Dp116 [55]. Therefore, alternative activation of translation initiation codons is highly possible in Dp116 transcripts.…”
Section: Dp118 Produced By Activation Of An Alternative Translation Imentioning
confidence: 97%